Strategic Challenges for NATO in an Evolving Global Security Landscape - Nazia Sheikh (ASIAN Journal of International Peace & Security (AJIPS), 2024)
Following the Russia-Ukraine war on February 24, 2022, the post-Cold War international order collapsed and the greatest crisis started in Europe since World War I. It is questionable whether NATO can maintain such a crucial position in the current situation. In light of the dynamically shifting global landscape, this paper explores the internal and external security threats to NATO in the 21st century. This study also examines the future of NATO in the face of new international security threats and critically analyzes what the alliance and its members need to do to stay relevant in the current strategic landscape. To guarantee NATO’s continued relevance and efficacy, the paper suggests improving the alliance’s technological capabilities, internal cohesion and strategic emphasis in response to emerging international security threats. Otherwise, NATO may gradually disintegrate as a military institution; however, due to the strength of the security community established among the allies, it will continue to exist as a political institution. In this study, a qualitative research approach is used to analyze primary and secondary data, applying both neo-realist and constructivist theories to examine an adaptation of neo-realist power struggles and constructivist institutional structures.